Analisis Kebolehan Wakaf Tunai Menurut Maqashid Syariah - Imam Kamaluddin; Muhammad Vicki Azhari (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2024)
Abstract Waqf has become one of the instruments in Islamic economics that has special specifications and is different from other types of philanthropy. Waqf has the characteristic of eternity, which means that if certain assets have been donated, it will not change until the end of the world. However, with the development of the era, a new form of waqf has emerged in the form of cash or cash waqf which is still a debate among scholars about its permissibility. This article aims to analyze the permissibility of cash waqf according to the maqashid sharia review. By using a literature review of writings explaining cash waqf and maqashid sharia, it can be concluded that cash waqf is considered permissible because it has many very important benefits for the country's economy, as a means of transferring the wealth of the rich to entrepreneurs and citizens in financing various religious, social, and educational programs in Islamic countries. Keywords: waqf, cash waqf, maqashid syariah.